Ageing across continents: Insights into the physical health of older adults with intellectual disability from Ireland and Australia. - Mc Mahon, Martin; Burke, Eilish (My University, 2025)
Chronic conditions and multimorbidity are prevalent in older people with intellectual disability. International comparisons of disease prevalence may reflect the heterogeneity of healthcare policy internationally and the distinct social histories of different countries. This study sought to determine if differences in patterns of disease prevalence in Ireland and Australia could elucidate effective and deficient aspects of policy and practice in each country. Data from existing and independent national studies in Ireland and Australia were matched on demography and diagnoses. The prevalences of 9 chronic conditions and multimorbidity across and within both jurisdictions were compared. p values were corrected for multiple hypothesis testing. Thyroid disorder, epilepsy and hypertension were more prevalent in Ireland. Arthritis was more prevalent in Australia. In Australia, arthritis, asthma, and thyroid disorder were more common in females. In Ireland, diabetes prevalence was more prevalent in females (11.9 times more likely than in males). The Irish population was 2.7 times more likely to be multimorbid compared to their Australian counterparts. In both countries, females were 2.6 times more likely to be multimorbid than males. The findings of this study offer unique insights into identifying and tracking multimorbidity and serve as a foundation for developing strategies to improve healthcare outcomes for this population. Differences such as increased prevalence rates of hypertension, epilepsy, and thyroid conditions were observed in the Irish cohort. Differences in multimorbidity trends and sex-stratified disease burden, emphasize the need for further investigation into the environmental, diagnostic, and systemic factors that influence outcomes. These findings highlight the differences in disease prevalence and multimorbidity between Ireland and Australia. There is a critical need for improved data harmonization and targeted interventions to address inequalities particularly sex-stratified diseases which disproportionately affect women with intellectual disability.
PUBLISHED
Keywords: Ageing; Health outcomes; Health status and inequalities; INTELLECTUAL DISABILITIES; Older people with intellectual disabilities; Patterns of health; Age-related disability; Chronic Health Condition; Intellectual Disability; Health; Third age/ageing